Enforcing integrity of agent migration paths by distribution of trust. (17th December 2009) - Warnier, Martijn; Oey, Michel; Timmer, Reinier; Brazier, Frances; , Benno Overeinder
Agent mobility is the ability of an agent to migrate from one location to another across a network. Though conceptually relatively straightforward, in practice security of mobile agents is a challenge: from transport layer security to preservation of integrity in open environments. This paper discusses the security issues involved and proposes protocols for secure agent migration. AgentScape, an agent platform for mobile agents, is used to illustrate the feasibility of the implementation of these protocols.